Same-Sex Parenting: Identification of Social Representations in a Sample of Portuguese Professionals. Issue 2 (28th January 2019) - Xavier, Paula; Alberto, Isabel; Mendes, Francisco
ABSTRACT: Although international scientific research and the position of professional associations reiterate that the parents' sexual orientation is not a criterion of parenting quality, the social recognition of same-sex parenting remains difficult in Portugal. Given the importance of forensic issues in this field, this study aims to identify the representations of psychologists, social workers, lawyers/attorneys, and judges regarding same-sex parenting. The study involves five homogeneous focus groups with a total of 19 professionals. Content analysis reveals reservations regarding same-sex couples' access to parenting, in particular among lawyers/attorneys. There also emerged narratives that highlight specific competencies in these families and that argue that sexual orientation does not define the quality of parenting. Social narratives are more expressive than scientific knowledge in support of professional representations. These findings have critical implications for professional practice and formation.